Pola Komunikasi Gender Dalam Keluarga - Nuraida Nuraida; Muhammad Zaki (Wardah, 2017)
This study focuses on the pattern of gender communication within the family. The purpose of this study is to analyze the gender communication pattern that is considered still inequality in the family. Four patterns of family communication consist of; Equality Pattern, Balance Split Pattern, Unbalance Split Pattern and Monopoly Pattern. The four patterns illustrate the division of roles and position of each member in the family. The findings in this study are the pattern of communication equation is the most supportive pattern in instilling gender values in the family because this pattern emphasizes equality among family members. Indeed, family relationships can be implemented depending on a number of factors, including: First, the number of interaction systems in the family should be considered. Second, family structure affects relationships. Third, family relationships are influenced by the nature of parents. Fourth, the distance between one and the other affects the relationship within the family. Although it is concurrently recognized that socio-cultural constructions continue to have a significant effect on the division of roles played by men (husband) and women (wife) in family institutions.